2016
DOI: 10.1111/jse.12225
|View full text |Cite
|
Sign up to set email alerts
|

A phylogeny of the genus Encyclia (Orchidaceae: Laeliinae), with emphasis on the species of the Northern Hemisphere

Abstract: Encyclia comprises over 150 species of orchids that occupy mainly seasonally dry habitats in tropical and subtropical America and are usually restricted to one or a few ecoregions. To determine whether species found in the same or neighboring ecoregions are closely related, we sampled more than 50 taxa, with an emphasis on species found in Mexico and Central America. We evaluated five DNA markers for their phylogenetic utility: the nuclear low copy gene PHYC, a plastid spacer region trnL‐F, a fragment of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 64 publications
0
12
0
2
Order By: Relevance
“…As revisited by Pinheiro and Cozzolino (2013), hybridization likely is a key process shaping the diversification of some groups of Epidendrum. Similar patterns of strongly-supported incongruence between nuclear and plastid partitions at shallow phylogenetic levels have been observed within most of the genera of Laeliinae that have been investigated using Sanger sequencing, e.g., Cattleya (van den Berg et al, 2009;van den Berg, 2014), Encyclia (Leopardi-Verde et al, 2017), andLaelia (Peraza-Flores et al, 2016). This seems to be caused by the combination of few genetic incompatibility barriers and very low variation in chromosome numbers across the subtribe, including Epidendrum (Felix and Guerra, 2010;De Assis et al, 2013), and confirmed by the large number of natural hybrids (including intergenerics) reported in the subtribe (Adams and Anderson, 1958;van den Berg, 2014).…”
Section: Phylogenetic Utility Of Nuclear and Plastid Locimentioning
confidence: 54%
“…As revisited by Pinheiro and Cozzolino (2013), hybridization likely is a key process shaping the diversification of some groups of Epidendrum. Similar patterns of strongly-supported incongruence between nuclear and plastid partitions at shallow phylogenetic levels have been observed within most of the genera of Laeliinae that have been investigated using Sanger sequencing, e.g., Cattleya (van den Berg et al, 2009;van den Berg, 2014), Encyclia (Leopardi-Verde et al, 2017), andLaelia (Peraza-Flores et al, 2016). This seems to be caused by the combination of few genetic incompatibility barriers and very low variation in chromosome numbers across the subtribe, including Epidendrum (Felix and Guerra, 2010;De Assis et al, 2013), and confirmed by the large number of natural hybrids (including intergenerics) reported in the subtribe (Adams and Anderson, 1958;van den Berg, 2014).…”
Section: Phylogenetic Utility Of Nuclear and Plastid Locimentioning
confidence: 54%
“…The recent diversification of Mexican vascular flora and its main lineages has been previously pointed out to be developed during the Miocene, between 5 and 20 mya (Sosa et al, 2018). Several of their descendants are present in the SMS, including some endemic species of the subfamily Hechtioideae (Bromeliaceae; Rivera‐Martínez et al, 2022), the tribes Eupatorieae and Heliantheae (Asteraceae; Schmidt & Schilling, 2000), the genera Agave (Asparagaceae; Good‐Avila et al, 2006), Bursera (Burseraceae; De‐Nova et al, 2012), Dahlia and Hidalgoa (Asteraceae; Sánchez‐Chávez et al, 2019), Fouquieria (Fouquieriaceae; De‐Nova et al, 2018), Encyclia (Orchidaceae; Leopardi‐Verde et al, 2016), Salvia subg. Calosphace (Lamiaceae; Fragoso‐Martínez et al, 2018) and Stevia (Asteraceae; Soejima et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that C. glaucoglossa and C. thylaciochila are known to share the same pollinator ( Eufriesea caerulescens ) and appear to retain their identities by placing the pollinaria on different parts of the pollinator: C. glaucoglossa on the head, C. thylaciochila on the dorsal section of the thorax (Aguirre León, 1979). As in several studies of plants (e.g., Leopardi‐Verde, 2014; Leopardi‐Verde & al., 2016; Bastos, 2014; Ramírez‐Morillo & al., 2018; Calonje & al., 2019; Pelser & al., 2019; Carnevali & al., in press), it becomes evident that biogeography is a better predictor of relationships than morphology (particularly floral morphology), probably because of local radiations to invade different pollination niches. In this particular case, the two Clowesia species that grow in the Balsas basin are florally very different (see taxonomic treatment), with C. thylaciochila almost indistinguishable from the allopatric, more distantly related C. dodsoniana (with which it had been confused in the past), whereas C. glaucoglossa has a unique labellar morphology that renders a superficial assessment of relationships difficult.…”
Section: Discussionmentioning
confidence: 99%